Cumulative Ecological Risk and Problem Behaviors Among Adolescents in Secondary Vocational Schools: The Mediating Roles of Core Self-Evaluation and Basic Psychological Need Satisfaction - Sun, Peizhen; Sun, Yudi; Fang, Delan; Jiang, Hongyan; Pan, Mengjie (Frontiers in Public Health, 2021)
Based on the Cumulative Risk Model, a single risk factor cannot play a decisive role, but the cumulative ecological risks may have complex superposition effects on adolescents’ problem behaviors. However, although many studies have investigated the specific influences of single external risk factors on problem behaviors, the effect of cumulative ecological risk on problem behaviors and especially the underlying mechanisms therein have been under-investigated. Therefore, this study aimed to explore the effect of cumulative ecological risk on adolescents’ problem behaviors, and the mediating effects of core self-evaluation and basic psychological needs satisfaction therein. To achieve this, 1080 adolescents in secondary vocational schools were surveyed with the questionnaires of cumulative ecological risk, basic psychological need satisfaction, core self-evaluation, externalizing and internalizing problem behaviors. Results showed that: (a) cumulative ecological risk was positively related with both internalizing problem behavior and externalizing problem behavior; (b) core self-evaluation and basic psychological need satisfaction not only respectively but also sequentially mediated the relationship between cumulative ecological risk and two sorts of problem behaviors. These results provide some pivotal implications for the precaution and intervention of the adolescent problem behaviors.